Characterization and Antioxidant Activities of Yellow Strain Flammulina velutipes (Jinhua Mushroom) Polysaccharides and Their Effects on ROS Content in L929 Cell - Yu-Ning Hu; Tzu-Jung Sung; Chun-Hsu Chou; Kai-Lun Liu; Liang-Po Hsieh; Chang-Wei Hsieh (MDPI AG, 2019)
Yellow strain Flammulina velutipes, which is known as Jinhua mushroom in Taiwan, has become popular among customers due to its distinct texture that is utterly different from white strain F. velutipes. However, there has been little study on the physicochemical properties, antioxidant activities, and biological functions of yellow strain F. velutipes polysaccharides (FVYs). The specific aims of this study are to evaluate and compare the physicochemical properties, antioxidant activities, and biological functions of FVYs and white strain F. velutipes polysaccharides (FVWs) in order to select the strain appropriate for cosmetic ingredient. The FVYs and FVWs were prepared by fractional precipitation (40%, 60%, and 80%). According to the results, FVY-80 showed the greatest antioxidant activities based on 2,2-diphenyl-1-picrylhydrazyl (DPPH) (IC50 = 2.22 mg/mL) and 2,2’ -azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS) radical assay (IC50 = 2.04 mg/mL). None of the fractions exhibited cytotoxicity toward L929 cell under a concentration of 500 <semantics> μ </semantics> g/mL. FVY-80 significantly reduced the reactive oxygen species (ROS) content in L929 cell by 55.96%, as compared with the H2O2-induced L929 cell, according to the dichloro-dihydro-fluorescein diacetate (DCFH-DA) assay. In conclusion, we suggest that FVY-80 is the best source for a cosmetics ingredient.